Employment and growth effects of tax reforms in a growth-matching model - Angela Birk; Jochen Michaelis (Hamburg Institute of International Economics (HWWA), 2002)
This paper explores how revenue-neutral tax reforms impact employment and economic growth in models of exogenous and endogenous growth and search frictions on the labor market. We show that (i) a cut in the payroll tax financed by an increase in the wage tax lowers both equilibrium employment and the equilibrium growth rate, that (ii) a higher energy tax combined with a cut in wage taxes boosts employment but has an ambiguous effect on growth, and that (iii) a higher energy tax combined with a cut in payroll taxes enhances employment but mitigates economic growth.
Keywords: E6; J6; H2; O4; 330; search unemployment; growth; tax reform; Steuerreform; Ökosteuer; Lohnsummensteuer; Steuerwirkung; Beschäftigungseffekt; Friktionelle Arbeitslosigkeit; Neue Wachstumstheorie; Theorie